Analysis of motorcycle vibration comfort based on rigid-flexible coupling model. (June 2020) - Feng, Yu; Jun, Xie
Based on the rigid-flexible coupling model, this article utilized ADAMS to establish a dynamics model of a motorcycle, in which the engine excitation and road excitation were determined. According to the ISO5349 and ISO2631 standards, the vibration of the motorcycle at 60 km/h was analyzed. The results showed that the high-frequency vibration of the engine accounted for the most vibration at the handle when driving on the B-class road at 60 km/h, and the vibration level was uncomfortable. In contrast, the low-frequency vibration of the road roughness was the main excitation of the cushion vibration, and the vibration level was relatively uncomfortable. These results were in accordance with the subjective impression on human observers, indicating that the vibration comfort analysis method based on the rigid-flexible coupling model was correct and effective to provide theoretical basis for the subsequent improvement and modification early in the design stage.